2009
DOI: 10.1164/rccm.200804-567oc
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as Supplementary Treatment for Tuberculosis

Abstract: Vitamin D does not improve clinical outcome among patients with TB and the trial showed no overall effect on mortality in patients with TB; it is possible that the dose used was insufficient. Clinical trial registered with www.controlled-trials.com/isrctn (ISRCTN35212132).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(147 citation statements)
references
References 28 publications
3
139
1
1
Order By: Relevance
“…Other possible explanations for differences in measured responses of human HIV ϩ macrophages to exogenous 1,25D 3 include differences in host defense gene expression induced by HIV infection, the requirement of TLR or other receptor expression to critical or threshold levels to activate signaling pathways, or differences in activation states of HIV ϩ macrophages compared to macrophages from healthy persons (48), although these were not specifically investigated in the current study. (49,50). Our central observation is that vitamin D pretreatment can rescue defective M. tuberculosis-mediated TNF release in HIV ϩ human macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible explanations for differences in measured responses of human HIV ϩ macrophages to exogenous 1,25D 3 include differences in host defense gene expression induced by HIV infection, the requirement of TLR or other receptor expression to critical or threshold levels to activate signaling pathways, or differences in activation states of HIV ϩ macrophages compared to macrophages from healthy persons (48), although these were not specifically investigated in the current study. (49,50). Our central observation is that vitamin D pretreatment can rescue defective M. tuberculosis-mediated TNF release in HIV ϩ human macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies on vitamin D supplementation in deficient individuals with active MTb have been disappointing. In a randomized, doubleblind, placebo-controlled trial involving patients with MTb in Guinea-Bissau, supplementation with vitamin D did not lead to an improvement in clinical severity or 12-month mortality (Wejse et al 2009). However, the relevance of this negative result is questionable given that the intervention did not influence participants' vitamin D status.…”
Section: Respiratory Infectionsmentioning
confidence: 99%
“…In one study, high-dose vitamin D supplementation was reported to accelerate clinical and radiological improvement in pulmonary tuberculosis patients [148]. However, others reported no effect [149]. A recent systematic review of randomized, placebo double-blind trials assessing the beneficial of vitamin D administration in patients with multiple sclerosis was unable to reach a verdict with no significant effect seen in 4 out of 5 available trials [150].…”
Section: Link Between Vitamin D and Immune Function - Evidence From Imentioning
confidence: 99%